Preparation method and application of PANI (at) single-layer graphene oxide / MWCNT material auxiliary electrode

The PANI@ single-layer graphene oxide/MWCNT material auxiliary electrode prepared by acid treatment of single-layer graphene oxide and multi-wall carbon nanotubes is solved by solving the problems of high cost and insufficient processing capacity of existing electric repair auxiliary electrode materials. , achieving efficient and economical soil pollutant removal effect.

CN119406908AActive Publication Date: 2025-02-11CHANGZHOU UNIV
View PDF 12 Cites 0 Cited by

Patent Information

Application Number
CN202411538183.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-31
Publication Date
2025-02-11
Estimated Expiration
2044-10-31

AI Technical Summary

Technical Problem

The existing soil electric repair auxiliary electrode materials have problems such as high loss of precious metals, high cost, weak electrocatalytic capacity, and insufficient treatment capacity, which affects the effective removal of soil pollutants.

Method used

After using acid to treat single-layer graphene oxide and multi-wall carbon nanotubes, PANI@ single-layer graphene oxide/MWCNT material auxiliary electrode was prepared by loading polyaniline (PANI). Through its conductive network and acid-modified carbon material functional groups, Improve electrocatalytic performance and electric repair effect.

Benefits of technology

It improves electrocatalytic performance and electric repair effect, reduces electricity consumption, enhances the treatment capacity of contaminated soil, and has low cost, good film formation and large specific surface area. It is suitable for heavy metal pollution treatment in soil.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119406908A_ABST
    Figure CN119406908A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of soil heavy metal electrokinetic remediation, and particularly relates to a preparation method and application of a PANI (at) single-layer graphene oxide / MWCNT material auxiliary electrode. According to the method, hydrochloric acid is used for carrying out acid treatment functionalization on two carbon materials, polyaniline is synthesized through aniline and loaded on the polyaniline to prepare an auxiliary electrode, and the carbon materials are single-layer graphene oxide and MWCNT (multi-walled carbon nanotubes). Under the synergistic effect of the acid-modified single-layer graphene oxide, the MWCNT and the PANI, the auxiliary electrode shows higher structural stability and more excellent electrochemical characteristics, and the high-order stabilization time experienced by electrokinetic remediation is longer. The auxiliary electrode prepared by the method has obvious advantages in the aspects of shape, conductivity and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of soil heavy metal electric remediation, and specifically relates to a preparation method and application of a PANI@single-layer graphene oxide / MWCNT material auxiliary electrode. Background Art

[0002] Soil pollution remediation faces problems such as high difficulty, long time consumption and high remediation cost. Many targeted soil remediation methods have been developed for different types of soil pollution. Electrokinetic remediation technology is a widely used in-situ soil remediation technology. Driven by the voltage gradient, pollutants in the soil are removed through electromigration, electrophoresis, electroosmosis and diffusion. Among them, the electromigration of ionic chemicals caused by the electric field during the electrokinetic remediation process is an important process for pollutant removal. In terms of treating contaminated soil, it has the characteristics of simple construction process and no secondary pollution. In recent years, it has been widely used in contaminated soil treatment projects. In order to enhance the electric field strength and increase the electrolysis effect during the electrokinetic remediation process, auxiliary electrodes are currently constructed without power supply, which can both strengthen the electric field and reduce energy consumption. Therefore, the development of effective auxiliary electrodes is of great significance to the removal of soil pollutants.

[0003] The current auxiliary electrode materials contain precious metals, such as the patent CN202211202336.7 carbon nanotube-assisted carbon-coated magnesium titanium phosphate electrode material. The main defects of the current auxiliary electrode materials are: the precious metals as auxiliary electrodes have huge losses and high costs; the ordinary graphite auxiliary electrode has weak electrocatalytic ability and low efficiency, which affects the cost of use; the metal auxiliary electrode will have problems such as metal precipitation and electrolyte pollution; other auxiliary electrodes without metals also have problems such as insufficient processing capacity, low current efficiency, and long repair time in electric repair. At this time, it is necessary to develop a new auxiliary electrode with low environmental interference, green environmental protection, and high economic benefits.

[0004] In view of the above problems, the present invention uses PANI material with semiconductor and conductor properties to load on two acid-modified carbon material surface materials (single-layer graphene oxide, MWCNT) to prepare a PANI@single-layer graphene oxide / MWCNT material auxiliary electrode. Summary of the invention

[0005] In view of the demand for efficient electrodes in the electric repair process, the present invention prepares a PANI@single-layer graphene oxide / MWCNT material to make an auxiliary electrode to enhance the electric repair effect.

[0006] The technical solution adopted by the present invention is: after acid treatment of monolayer graphene oxide and MWCNT (multi-walled carbon nanotube), AN (aniline) is synthesized into PANI (polyaniline) and loaded on two acid-modified carbon materials. The present invention uses monolayer graphene oxide and MWCNT materials as the main auxiliary electrode raw materials, and after acid treatment of the two carbon materials, AN is used to synthesize PANI and then loaded to prepare a new auxiliary electrode for electrokinetic remediation of pollutants in soil.

[0007] The principle of the present invention is: after acid treatment of two carbon materials (monolayer graphene oxide, MWCNT), the monolayer graphene oxide has a variety of oxygen-containing hydrophilic functional groups such as hydroxyl, carboxyl and epoxy groups in its structure, and these functional groups can be modified by chemical reaction, thereby giving the monolayer graphene oxide new properties, and MWCNT (multi-walled carbon nanotube) itself also has many good tube diameters and carries CN bonds, CH and CO bonds, and shows a good and stable CNT structure and connection support of oxygen-containing functional groups after acid treatment. Since there is no situation where heavy metals on the electrode surface are resolved to pollute the electrolyte, the two carbon materials as auxiliary electrode matrix materials will have more application prospects than current electrode materials. Polyaniline (PANI) as an electrode material has the advantages of high theoretical specific capacity, good chemical stability, simple preparation method, etc., and by compounding PANI and carbon materials, the problems of poor rate performance and cycle stability of PANI can be effectively compensated. The present invention uses acid-modified single-layer graphene oxide and MWCNT as a matrix material to load PANI to prepare an auxiliary electrode, which can greatly improve the electrocatalytic performance and electrokinetic remediation effect, reduce the energy consumption of electrokinetic remediation, and improve the contaminated soil treatment capacity.

[0008] The method for preparing the PANI@single-layer graphene oxide / MWCNT material auxiliary electrode comprises the following steps:

[0009] (1) Preparation of acid-treated monolayer graphene oxide and MWCNT matrix materials: Mix hydrochloric acid solution and ultrapure water to prepare HCl aqueous solution; weigh MWCNT material in a beaker and use a humidifier device to moisten for 1 minute to eliminate static electricity inside the multi-walled carbon nanotube electrode, wait for 60 minutes, weigh monolayer graphene oxide powder and add it to the MWCNT material, add HCl aqueous solution and stir until uniformly mixed, and seal and stir for 12 hours;

[0010] The ratio of MWCNT, monolayer graphene oxide, hydrochloric acid solution (concentration 36-38 wt%), and ultrapure water is 6 g: 0.25-1 g: 25 mL: 100 mL;

[0011] (2) Preparation of AN solution: Mix hydrochloric acid solution and ultrapure water to prepare HCl aqueous solution; extract a certain amount of AN liquid, put it into the HCl aqueous solution and shake it to obtain AN-HCl solution; wherein the amount ratio of MWCNT, AN, hydrochloric acid solution (concentration 36-38wt%), and ultrapure water is 6g:1-2mL:25mL:100mL.

[0012] (3) Slowly adding the AN-HCl solution prepared in step (2) into the solution obtained in step (1), and then sealing and stirring for 12 h;

[0013] (4) Weigh a certain amount of APS (ammonium persulfate) and dissolve it in ultrapure water to prepare an APS solution; in an ice bath state (0°C to 5°C), drop the APS solution into the solution obtained in step (3) at a rate of 3 to 5 seconds per drop for a time of 1.75 to 2.25 hours, and then stir for 8.75 hours to 9.25 hours;

[0014] Among them, the mass ratio of MWCNT, APS, and ultrapure water is 6:2.28-3.42:100;

[0015] (5) The mixed solution obtained in step (4) was filtered and then placed in a vacuum drying oven at a constant temperature of 75° C. and dried for 12 h to obtain a PANI@single-layer graphene oxide MWCNT material;

[0016] (6) Preparation of auxiliary electrode material: Weigh the binder (C3H3NaO2) n After grinding through a 80-100 mesh sieve, it is mixed evenly with the PANI@ single-layer graphene oxide MWCNT material and placed in a die-casting. Under pressure, a square sheet electrode can be formed, wherein (C3H3NaO2) n , the mass ratio of single-layer MWCNT is 0.8-1.2:6; because single-layer graphene oxide and MWCNT and PANI have strong pressure resistance and are not easy to tear, the auxiliary electrode material has extremely strong plasticity.

[0017] As a preferred experimental scheme of the present invention, the resistivity of the ultrapure water is greater than 18 MΩ×cm (25° C.).

[0018] Furthermore, in step (1), the MWCNT material needs to be treated by humidification to eliminate static electricity, otherwise it cannot effectively contact with the monolayer graphene oxide powder;

[0019] As a preferred experimental scheme of the present invention, in step (1), the ratio of MWCNT: single-layer graphene oxide, hydrochloric acid solution (concentration 36-38wt%), and ultrapure water is 6:0.25:25mL:100mL;

[0020] As a preferred experimental scheme of the present invention, in step (1), the ratio of MWCNT, single-layer graphene oxide, hydrochloric acid solution, and ultrapure water is 6 g: 0.25 g: 25 mL: 100 mL;

[0021] As a preferred experimental scheme of the present invention, in step (1), the purity of the MWCNT material is >99%;

[0022] As a preferred experimental scheme of the present invention, in step (1), the diameter of the single-layer graphene oxide sheet is 0.5-5 μm, the thickness is 0.8-1.2 nm, and the purity is ≈99%;

[0023] As a preferred experimental scheme of the present invention, in step (2), the ratio of MWCNT, AN, HCl solution (concentration 36-38%), and ultrapure water is 6 g: 1.17 mL: 25 mL: 100 mL;

[0024] As a preferred experimental scheme of the present invention, in step (4), the mass ratio of MWCNT, APS and ultrapure water is 6:2.9:100; further, in step (5), the filtration membrane is selected from 0.45PTFE membrane, and the filtration is completed after washing with ultrapure water three times;

[0025] Further, in step (6), (C3H3NaO2) n Average Mw: 3 million to 7 million; Grind and sieve agate;

[0026] Furthermore, in step (6), an infrared tablet press (pressure value Max = 30 tons) is used for pressing, and the size of the mold is 5 cm × 3.5 cm × 3 cm;

[0027] As a preferred experimental scheme of the present invention, in step (10), the auxiliary electrode material is pressed using a pressure of 27 tons;

[0028] The present invention has the following advantages and technical effects:

[0029] 1. The present invention uses acid-modified single-layer graphene oxide and MWCNT as matrix materials to load PANI, and uses it to make a new auxiliary electrode, which is used to solve the problem that the current size is limited during the soil electrokinetic remediation process, so that the electrokinetic remediation process is long and the power loss is too high, and the current of the electrokinetic remediation can be quickly climbed to the peak. The acid-modified single-layer graphene oxide and MWCNT fully introduce defect sites and attach necessary functional groups (such as hydroxyl and carboxyl groups), and the PANI load can fill the gaps in the carbon material and form a conductive network of intricate loads. Under the synergistic effect of the acid-modified single-layer graphene oxide and MWCNT and PANI, the auxiliary electrode prepared in particular exhibits higher structural stability and more excellent electrochemical properties, prolongs the high-level stable time experienced by electrokinetic remediation (the time when the current is greater than 110mA), improves the treatment effect of heavy metal pollution in contaminated soil, can be used for the comprehensive advantages of Cu heavy metal ion water treatment, and enhances the effect of electrokinetic remediation of soil.

[0030] 2. The PANI@single-layer graphene oxide / MWCNT material auxiliary electrode prepared by the present invention has a larger specific surface area compared to traditional auxiliary electrodes, such as carbon rods and graphite electrodes, and can greatly increase the current to promote the migration of heavy metals in contaminated soil. Since the PANI@single-layer graphene oxide / MWCNT material auxiliary electrode has the characteristics of low preparation cost, good film-forming property, large specific surface area, and easy functionalization, there is no situation where heavy metals on the electrode surface decompose and pollute the electrolyte, and it has a relatively broad application prospect in the treatment of heavy metal pollution in soil. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the following is a brief introduction to the drawings required for the description of the embodiments. The drawings described herein are used to provide a further understanding of the present invention and constitute a part of the present invention. The schematic embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation on the present invention. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0032] Figure 1 This is a photo of the auxiliary electrode prepared in Example 1, which is placed in a plastic bag with the specifications of length: 5 cm, width: 3.5 cm, thickness: 0.2 cm;

[0033] Figure 2 The cyclic voltammetry (CV) curve of the auxiliary electrode prepared in Example 1 in a mixed solution of 0.1 mol / L K3Fe(CN)6 and 0.1 mol / L NaCl, wherein a saturated calomel electrode is used as a reference electrode and a silver chloride electrode is used as an auxiliary electrode;

[0034] Figure 3 The auxiliary electrode prepared in Example 1 and the auxiliary electrode material prepared in Comparative Example 1 are X-ray diffraction (XRD) images of the auxiliary electrode material prepared in Example 1, wherein the peak at 2θ=5° to 80° corresponds to the crystalline characteristics, wherein (a) is Example 1, and (b) is Comparative Example 1;

[0035] Figure 4 is the FTIR spectrum image of the auxiliary electrode material prepared in Example 1, and the distribution and value of specific peaks are marked;

[0036] Figure 5 It is an image of the soil electroremediation device, showing the location of the auxiliary electrode and the size of the electroremediation device;

[0037] Figure 6 This is the preparation flow chart of PANI@single-layer graphene oxide MWCNT material. DETAILED DESCRIPTION

[0038] In order to make the purpose, technical solutions and advantages of the embodiments of the present application clearer, the technical solutions in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments.

[0039] Based on the embodiments in the present application, all other embodiments obtained by those of ordinary skill in the art without making creative work, all belong to the scope of protection of the present application. Unless otherwise stated, all technical and scientific terms used herein have the same meanings as those of ordinary skill in the field of the present invention are generally understood. Although the present invention only describes preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. In the event of conflict with any incorporated document, the content of this specification shall prevail.

[0040] Example 1

[0041] a. Weigh a certain amount of multi-walled carbon nanotubes (MWCNT) 6g into a 500mL beaker and use a humidifier to moisten for 1min, then wait for 60min to eliminate the static electricity inside the multi-walled carbon nanotube electrode, weigh 0.25g of single-layer graphene oxide and sprinkle it evenly into it and mix it evenly. The mass ratio of MWCNT to single-layer graphene oxide is 6:0.25;

[0042] b. Weigh 25 mL of hydrochloric acid (HCl concentration 36 wt%) solution and 100 mL of ultrapure water to make an HCl aqueous solution, add it to the beaker containing the mixture of MWCNT and monolayer graphene oxide, mix well, seal and stir for 12 h to form an acid-modified monolayer graphene oxide and multi-walled carbon nanotube composite solution;

[0043] c. Take 25 mL of hydrochloric acid (HCl concentration 36 wt%) solution and mix with 100 mL of ultrapure water to prepare an aqueous solution of HCl. Add 1.17 mL of aniline (AN) dropwise into the aqueous solution of HCl and shake well to obtain an AN-HCl solution.

[0044] d. Weigh 2.9 g of ammonium persulfate (APS) and add 100 mL of ultrapure water to dissolve it to prepare an APS aqueous solution;

[0045] e. Add the AN-HCl solution to the acid-modified monolayer graphene oxide and multi-walled carbon nanotube composite solution, put it into the rotor and seal it, and stir for 12 hours until it is evenly mixed;

[0046] f. The APS aqueous solution was transferred to a titration apparatus, the apparatus was kept in an ice bath state (0°C to 5°C), the titration apparatus was controlled at a rate of 3 seconds / drop, and the mixed solution obtained in step e was dripped while using magnetic stirring. The titration time was completed for 2.0 hours, and then the magnetic stirring time was 9.0 hours;

[0047] g. After completion, use a vacuum filter pump to filter through a 0.45 PTFE membrane and then put it into a drying oven. Set the drying oven temperature to 75°C and dry it for 12 hours to obtain PANI@single-layer graphene oxide MWCNT material;

[0048] h. Weigh the binder ((C3H3NaO2) n ) has a mass of 0.8 g and is ground through an 80-mesh sieve;

[0049] i. Add the ground ((C3H3NaO2) n ) and the PANI@single-layer graphene oxide MWCNT material are uniformly mixed;

[0050] j. Tablet pressing: The die-casting mold with specifications of 5cm×3.5cm×3cm is used, and an infrared tablet press with a pressure of 27 tons is used to make the material into a sheet to obtain an auxiliary electrode;

[0051] Comparative Example 1

[0052] The comparative auxiliary electrode 2 was prepared according to the steps of Example 1. The difference between Comparative Example 1 and Example 1 is that the volume of AN added is 0.59 mL, and the rest is the same as Example 1.

[0053] Test Case

[0054] The prepared auxiliary electrode was characterized in terms of morphology and electrochemistry. The test examples of the present invention are further described in detail below in conjunction with the accompanying drawings.

[0055] Figure 2The CV curve of the auxiliary electrode material prepared in Example 1 in 0.1mol / L K3Fe(CN)6+0.1mol / LNaCl solution. The diameters of the working electrode, reference electrode and counter electrode (saturated calomel electrode as reference electrode, silver chloride electrode as auxiliary electrode) are 6mm, 1mm and 1mm respectively. At -1.0V to 1.8V, the CV curve maintains a closed shape without obvious deformation, indicating an ideal double-layer capacitor behavior, with high ion and electronic reversibility and fast charge transfer capability. It is worth noting that the curve is almost symmetrical and slightly distorted, and the material exhibits excellent redox properties.

[0056] Figure 3 (a) shows the X-ray diffraction (XRD) image of the polyaniline prepared in Example 1 loaded on two acid-modified carbon materials. As shown in the figure, no diffraction peaks at 2θ=11.24° and 35.8° were observed, which indicates that the aniline monomer replaced the substance on the original carbon material after acid modification. Figure 3 (b) is the comparative auxiliary electrode 2 prepared in Example 2, and its AN dosage is reduced to 1 / 2 of that in Example 1. The diffraction peaks of the two images mainly appear at 2θ=12.1° and 25.28°. The diffraction peak at 25.28° is sharper due to the superposition of the intensity of polyaniline, indicating that polyaniline has a certain degree of crystallinity, but the amorphous structure of polyaniline usually inhibits its electrochemical performance, resulting in a wider peak shape. Since the AN dosage of the comparative auxiliary electrode 2 is not as much as that of the auxiliary electrode of the present invention, the peak area presented is smaller, and the synthesized PANI is not enough to make the crystallinity superposition more. It can be considered that a good crystal structure is conducive to the improvement of electrochemical performance.

[0057] Figure 4 The FTIR spectrum image of the auxiliary electrode prepared in Example 1 shows that the characteristic peak mainly appears at 3429 cm -1 、1560cm -1 、1489cm -1 、1307cm -1 and 1127cm -1 The main components of polyaniline are benzene ring and quinone ring. The stretching vibration of N-H bond is at 3429cm -1 、1560cm -1 and 1489cm -1 1307cm is the stretching vibration peak of C=C in the quinone ring and benzene ring structure; -1 The absorption peak at 1127cm is caused by the stretching vibration of C—N related to the benzene ring in the diquinone structure of polyaniline; -1 The strong absorption peak at is caused by the in-plane bending vibration of the C—H bond, corresponding to the intrinsic structure, and polyaniline is successfully synthesized on the surface of the acid-modified carbon material.

[0058] Application Examples

[0059] Application of auxiliary electrodes in electrokinetic soil remediation:

[0060] (1) Preparation of contaminated soil: The yellow-brown soil was excavated and naturally air-dried for 7 days to remove various impurities, plant roots, gravel, etc.; it was sieved through a 20-mesh sieve and stirred with water every day to form a thin mud. After adding CuSO4·5H2O, it was placed in a 150℃ oven and sintered for 24 hours.

[0061] (2) Preparation of aged contaminated soil: The contaminated soil was aged at room temperature for 60 days to obtain aged contaminated soil. The aged contaminated soil was placed in a planetary ball mill at a weight of 700 g / portion and the rotation speed was adjusted to 3500 r / min for a total of 60 min. The aged contaminated soil was ground through a 100-mesh sieve to obtain the prepared aged contaminated soil. The mass of CuSO4·5H2O in the soil was 0.2852 g. The purpose was to simulate the environment of electroplating sludge and other heavy metal contaminated soils.

[0062] (3) Placing the auxiliary electrode in the soil for soil remediation. Figure 5 The auxiliary electrode is not in contact with the electric repair device and is not powered. The middle soil area is divided into five contaminated areas: S1, S2, S3, S4, and S5. The cathode liquid, anode liquid, and electrolyte of the electric repair are 0.1 mol / L NaCl solutions. Graphite electrodes are used as cathodes and anodes. Ordinary graphite auxiliary electrodes (comparative auxiliary electrode 1), auxiliary electrodes prepared in Example 2 (comparative auxiliary electrode 2), or auxiliary electrodes prepared in Example 1 are added and placed in the anode liquid without power, and the changes in various parameters during the electric repair process are tested.

[0063] Table 1 shows the current changes of the auxiliary electrode prepared by the comparative auxiliary electrode 1 and the auxiliary electrode prepared by Example 1 during the 7-day electrokinetic repair process.

[0064] Table 1

[0065]

[0066] Compared with the current in the electric remediation using the auxiliary electrode of Example 1 (current>110mA time / total time), the ordinary graphite auxiliary electrode enhanced the electric remediation effect by about 39%, maintained a stable state for 7000min and then showed a slight downward change. The most important thing is that the auxiliary electrode of the present invention can make the current climb to the current peak more quickly and the current high time is longer than other auxiliary electrodes compared with other carbon material auxiliary electrodes. From the perspective of the electric remediation process as a whole, the auxiliary electrode made of the present invention has reliable practical value in enhancing the electric remediation of pollutants.

[0067] Tables 2 and 3 show the distribution of heavy metal Cu(II) in five partitions before and after 7 days of soil electrokinetic remediation using the comparative auxiliary electrode 1, comparative auxiliary electrode 2, and the auxiliary electrode prepared in Example 1.

[0068] The AAS test was used to measure the heavy metal content. About 1g of the soil-water mixture was taken out from 5 partitions, diluted 10 times and hydrochloric acid was added to dissolve the Cu ions. The mixture was shaken on a shaker for 6 hours and then separated from the soil and water by a low-speed centrifuge at 4800r / min for a total of 15 minutes, and the supernatant was measured.

[0069] The area size of the comparison repair electrode is the same as that of the auxiliary electrode in Example 1, so as to eliminate the experimental error caused by the difference in area.

[0070] Table 2

[0071]

[0072] After electric repair, the heavy metal content decreased significantly. The processing capacity of the auxiliary electrode prepared in Example 1 was 1.5 to 2.25 of that of the comparative auxiliary electrode 1.

[0073] Table 3

[0074]

[0075]

[0076] After the electric repair, the heavy metal content decreased significantly. From the perspective of each area, the auxiliary electrode of Example 1 has a higher treatment efficiency for heavy metal Cu than the comparative auxiliary electrode 2, and the overall effect is better than the comparative auxiliary electrode 2.

[0077] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.

Claims

1. A method for preparing a PANI@single-layer graphene oxide / MWCNT material auxiliary electrode, characterized in that: The following steps are involved: (1) mixing hydrochloric acid solution and ultrapure water to prepare an HCl aqueous solution; weighing a single-layer graphene oxide powder and adding it to the MWCNT material, adding the HCl aqueous solution, mixing evenly, sealing and stirring to form an acid-modified single-layer graphene oxide and multi-walled carbon nanotube composite solution; (2) AN, hydrochloric acid solution, and ultrapure water are shaken and mixed to obtain an AN-HCl solution; the AN-HCl solution is slowly added to the acid-modified single-layer graphene oxide and multi-walled carbon nanotube composite solution, mixed evenly, and then sealed and stirred; (3) dissolving APS in ultrapure water to prepare an APS solution; placing the solution obtained in step (2) in an ice bath at 0-5°C, adding the APS solution dropwise while stirring, and then stirring and reacting for a period of time, filtering, and drying to obtain a PANI@single-layer graphene oxide MWCNT material; (4) Add the binder (C3H3NaO2) n After grinding and sieving, the mixture is evenly mixed with the PANI@single-layer graphene oxide MWCNT material, and then pressed into an electrode to obtain a PANI@single-layer graphene oxide MWCNT material auxiliary electrode.

2. The method for preparing the PANI@single-layer graphene oxide / MWCNT material auxiliary electrode according to claim 1, characterized in that: The concentration of the hydrochloric acid solution in step (1) is 36-38 wt%; And / or, the usage ratio of the MWCNT, single-layer graphene oxide, hydrochloric acid solution, and ultrapure water is 6 g: 0.25 g to 1 g: 25 mL: 100 mL.

3. The method for preparing the PANI@single-layer graphene oxide / MWCNT material auxiliary electrode according to claim 1, characterized in that: The sealing stirring time in step (1) and step (2) is 12 hours.

4. The method for preparing the PANI@single-layer graphene oxide / MWCNT material auxiliary electrode according to claim 1, characterized in that: The concentration of the hydrochloric acid solution in step (2) is 36-38 wt%; And / or, the usage ratio of the MWCNT, AN, hydrochloric acid solution, and ultrapure water is 6 g: 1-2 mL: 25 mL: 100 mL.

5. The method for preparing the PANI@single-layer graphene oxide / MWCNT material auxiliary electrode according to claim 1, characterized in that: The mass ratio of MWCNT, APS and ultrapure water in step (3) is 6:2.28 to 3.42:

100.

6. The method for preparing the PANI@single-layer graphene oxide / MWCNT material auxiliary electrode according to claim 1, characterized in that: The dripping time in step (3) is 1.75 to 2.25 hours; And / or, the stirring reaction time in step (3) is 8.75h to 9.25h.

7. The method for preparing the PANI@single-layer graphene oxide / MWCNT material auxiliary electrode according to claim 1, characterized in that: The mass ratio of MWCNT and (C3H3NaO2)n in step (4) is 6:0.8~1.

2.

8. A PANI@single-layer graphene oxide / MWCNT material auxiliary electrode prepared by the method according to any one of claims 1 to 7.

9. Use of the PANI@single-layer graphene oxide / MWCNT material auxiliary electrode according to claim 8 in electrokinetic soil remediation.

Citation Information

Patent Citations

  • Carbon nanotube-assisted carbon-coated titanium magnesium phosphate electrode material as well as preparation method and application thereof

    CN115425213A

  • Graphene-carbon nanotube composite material, and preparation method and application thereof

    CN103779097A

  • Graphene composite electrode material and preparation method and application thereof

    CN103839698A

  • Polyaniline / carbon nanotube composite electrode material and preparation method thereof

    CN104091695A

  • Polyacid / polyaniline / carbon nano tube electrode material as well as preparation method and application thereof

    CN104332597A